The culture of permadeath: Roguelikes and Terror Management Theory. Issue 2 (1st June 2017) - Parker, Rob
In this exploratory article, Rob Parker examines the function of permadeath in the roguelike subgenre of computer role-playing games (cRPGs) through the lens of Terror Management Theory (TMT). In doing so, he provides a broad history of the subgenre, with specific attention to providing a productive distinction between modern and traditional roguelikes that lies in how they handle permadeath. He suggests that this focus on permadeath is one of the primary motivating factors for the resilience of the roguelike community over time, and what the implications of those motivations might mean for other members of the gaming community.